Generating New Meanings Through Metonymy in Colombian Slang (Parlache) - Pérez Sánchez, Juan Manuel (Íkala, Revista de Lenguaje y Cultura, 2009)
Taking into consideration the impact that semantic change has on slang, we analyse the role metonymy plays as a mechanism for generating new meanings in the youth slang of Medellín (Colombia), also known as parlache. As a starting point, the concepts “slang” and “metonymy” are delimited. Following these clarifications, a sample of twelve argotic meanings generated through metonymic processes of existing units is analysed. The results obtained after the analysis evidence tendencies in the use of certain types of metonymy within the sample. Likewise, tendencies in the choice of source concepts seem to be based on universal cognitive principles such as “typical over non-typical,” “bodily over mental,” and “concrete over abstract,” among others. Received: 29-08-08/ Accepted: 04-12-08 How to reference this article: Perez Sanchez, J. M. (2009). Generación de nuevos significados, mediante la metonimia, en el parlache. Íkala. 14(1), pp.13-35.